Theoretical study of methane adsorption on graphite - Albesa, Alberto Gustavo (2007)
In the present contribution, we performed PM3 semi – empirical and DFT calculations of increasing numbers of adsorbed methane molecules on a planar polyaromatic substrate, which mimics a graphene plane. In this way we attempt to describe low coverage methane adsorption on a graphite surface. Results show a configuration change of adsorbed molecules from hexagonal to square array as the coverage increases; however methane molecules distance to the surface remains almost unchanged for PM3 and for DFT diminishes from 4.2 A for one molecule to 3.8.